2010
DOI: 10.1177/0884533610379851
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status in Gestational Diabetes Mellitus

Abstract: These results suggested that rates of vitamin D deficiency are higher among women with IGT/GDM, and the relationship between vitamin D status and glucose tolerance in pregnancy needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
5
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 18 publications
9
87
5
4
Order By: Relevance
“…In a case-control study, Zhang et al, showed that in 16-week pregnant women with lower level of serum 25(OH)D, the risk of GDM was higher. 19 In another case-control study in Iran, it has been shown that women with GDM were 2.7 times more likely to display the low level of serum 25(OH)D. 17 In two other studies Baker et al and also Farrant et al , reported no association between serum 25(OH)D levels and the GDM development among pregnant women. 20,10 In a retrospective study, Makgoba reported no significant differences in serum level of vitamin D in GDM and non-GDM pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control study, Zhang et al, showed that in 16-week pregnant women with lower level of serum 25(OH)D, the risk of GDM was higher. 19 In another case-control study in Iran, it has been shown that women with GDM were 2.7 times more likely to display the low level of serum 25(OH)D. 17 In two other studies Baker et al and also Farrant et al , reported no association between serum 25(OH)D levels and the GDM development among pregnant women. 20,10 In a retrospective study, Makgoba reported no significant differences in serum level of vitamin D in GDM and non-GDM pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prevalence of hypovitaminosis D in pregnant women was 40%-100% in Sweden, 12 Australia, 13 Pakistan, India, 14 Japan 15 and China. 16 The prevalence of vitamin D deficiency in pregnant women in Yazd was reported to be 78.4% 17 and in Tehran it was 70.6%. 8 The difference in prevalence of vitamin D in pregnant women in different regions may be due to season of sampling, different methods of assaying serum vitamin D level, ethnics and genetic characteristics of the participants, geographical factors and other biologic factors that may affect on the heterogeneity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, no significant correlations were found between the deficiency of 25(OH)D and fasting glucose and 2-h glucose concentration during OGTT. Observations carried out globally in women with GDM drew attention to a significantly lower maternal 25(OH) D concentration determined in gestation week 24 to 28 than in pregnant women with normal glycaemia [1]. Studies from US and Iran showed that women with 25(OH)D levels < 25 vs. ≥ 25 nmol/L had significantly increased odds of GDM and higher blood glucose levels after 1-h oral glucose challenge test (OGCT) [3,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports have been published drawing attention to the coincidence between a low level of 25 (OH)D and presence of GDM [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies confirmed this significant relation. In Iran (2010), Soheilykhah et al conducted a matched case control study among 54 pregnant women; they reported a significant lower vitamin D level in (83%) GDM women compared with non-GDM (Soheilykhah et al, 2010). Parlea et al conducted a nested case-control study among 345 pregnant women (116 GDM & 219 non-GDM) and they reported significant lower vitamin D serum level in GDM group (56.3 vs. 62.0 nmol⁄ l, P = 0.018) (Parlea et al, 2012).…”
Section: Data Are Presented As Mean +/-Sd (Minimum -Maximum)mentioning
confidence: 99%